Advances in planar lipid bilayers and liposomes. - Iglic, Ales; Kulkarni, Chandrashekhar (Academic Press, 2013)
Advances in Planar Lipid Bilayers and Liposomes cover a broad range of topics, including main arrangements of the reconstituted system, namely planar lipid bilayers as well as spherical liposomes. The invited authors present the latest results of their own research groups in this exciting, multidisciplinary field. Incorporates contributions from newcomers and established and experienced researchersExplores the planar lipid bilayer systems and spherical liposomes from theoretical and experimental perspectivesServes as an indispensable source of information for new scientists.